Development of safety assessment system for food premises - Nazmi Imran, Makhilan; Nur Syafiqah, Fauzan; Nurhayati, Shariffudin; Amiruddin, Mohd Zin (Penerbit Universiti Malaysia Pahang, 2021)
Food safety issues have arising nowadays due to the lack of knowledge, attitude and practice (KAP) among food handlers. Lacking compliance among food handlers and food premises with the regulations and guidelines is also one of the causes that contribute to foodborne disease. Besides, lacking a systematic safety assessment system for food premises has hindered the improvement of food safety levels at the workplace. The study focuses on the development of a safety assessment system for food premises based on the Guideline for Grading System for Food Premises in Local Authority. The Safety Assessment System was developed by using Microsoft Excel. Validation of the system was conducted by getting feedback from food safety experts among government servants for further improvement. The System Usability Scale (SUS) test was done among two expert panels and the owner of food premises. The score for the SUS Test achieved 69.6 which is Grade C. The finding reveals that the developed system is considered above the average level, useable and succeeded.